Potato Island Site, District of Kenora, Ontario - Koezur, Polly (Book collections on Project MUSE., 1976)
Report of excavation, with analysis and comment, of the Potato Island site (ElKc-1) located near the headwaters of the English, Berens and Albany river systems in the District of Kenora, northern Ontario.